Internal accounting: analysis of the perception of footwear businesses on internal accounting in the city companies of Nova Serrana – MG (Research, Society and Development, 2019)
This study aims to verify managers’ view in relation to the implementation of internal accounting in footwear companies in Nova Serrana - MG. The research presents the importance of accounting in companies as an indispensable tool in the management process, aiming to unite accountant and businessman, obtaining several advantages as accessible and important information, which are necessary in the decision-making process. To answer the research question and achieve the proposed goals, we applied questionnaires to businessman in the footwear sector of Nova Serrana, in order to highlight the perception regarding the internal accounting. The main goal is to analyze the perception that businessman have with the implementation of accounting, whether or not it is viable for companies, whether it can reduce or increase costs in its purpose. The main results were that in the perception of businessman, internal accounting represents a high cost, reporting that only the administrative sector would experience a greater improvement as a result of this implementation, and that there would be approximation between businessman, assisting managers in the internal and external decision-making of the company.